PENGARUH TOTAL ASSET TURNOVER, CASH RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT ASTRA INTERNATIONAL TBK PERIODE 2013-2022 - Putri Dinanti, Dhara; Janudin (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of Total Asset Turnover, Cash Ratio and Debt To Asset Ratio on Return On Assets at PT. Astra International Tbk. Period 2013 – 2022 either partially or simultaneously. The method used is a quantitative method. The sample used is the financial report of PT. Astra International Tbk. In Jakarta for 10 years. Data analysis uses classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of the partial Total Asset Turnover research can be concluded to have a positive and significant effect on Return On. Cash Ratio partially has a negative and insignificant effect on Return On. Debt To Asset Ratio partially has a negative and significant effect on Return On Assets. The results of simultaneous testing of Total Asset Turnover, Cash Ratio, Debt To Asset Ratio have a positive and significant effect on Return On. The results of the coefficient of determination meaning that together the influence of Total Asset Turnover, Cash Ratio and Debt To Asset Ratio on Return On Assets.